High‐Pressure Single‐Crystal Elasticity and Thermal Equation of State of Omphacite and Their Implications for the Seismic Properties of Eclogite in the Earth's Interior. Issue 3 (2nd March 2019) - Hao, Ming; Zhang, Jin S.; Pierotti, Caroline E.; Ren, Zhiyuan; Zhang, D.
Abstract: Omphacite is a major mineral phase of eclogite, which provides the main driving force for the slab subduction into the Earth's interior. We have measured the single‐crystal elastic moduli of omphacite at high pressures for the first time up to 18 GPa at ambient temperature using Brillouin spectroscopy. A least squares fit of the velocity‐pressure data to the third‐order finite strain equation of state yields K S0 ′ = 4.5 (3), G 0 ′ = 1.6 (1) with ρ 0  = 3.34 (1) g/cm 3, K S0  = 123 (3) GPa, and G 0  = 74 (2) GPa. In addition, the synchrotron single‐crystal X‐ray diffraction data have been collected up to 18 GPa and 700 K. The fitting to Holland‐Powell thermal‐pressure equation of state yields K T0 ′ = 4.6 (5) and α 0  = 2.7 (8) × 10 −5  K −1 . Based on the obtained thermoelastic parameters of omphacite, the anisotropic seismic velocities of eclogite are modeled and compared with pyrolite between 200 and 500 km. The largest contrast between the eclogite and pyrolite in terms of seismic properties is observed between ~310 and 410 km. Key Points: Thermal equation of state and single‐crystal elasticity measurements is performed on omphacite crystals With the newly obtained thermoelastic parameters of omphacite, anisotropic seismic properties of eclogite are modeled The maximum Vp, Vs, and anisotropy contrast between pyrolite and eclogite is between 310 and 410 km